The Impact of Science Learning Multiliteration Model Based on Futuristic Pedagogic Approach to Metacognition Ability of Basic School Students - Herlambang, Yusuf Tri; Abidin, Yunus; Hernawan, Asep Herry; Setiawan, Dadan (International Conference on Elementary Education, 2020)
Developing metacognition abilities is one of the main goals in education. The ability of metacognition is one of the abilities that a person must have in the 21st century. The purpose of this study is to describe the impact of implementing a scientific multiliteration learning model on the metacognition abilities of elementary school students. The research method used in this study is a quasi-experimental method. The number of samples of this study were 39 students. Data were collected using an open-ended question test to measure the metacognition abilities of elementary school students. Data were analyzed through normality test, homogeneity test and t test using SPSS version 20.0 for windows. Based on the results of the study, it was found that the pre-test score of metacognition ability of elementary school students was 36.15 while the post-test score of metacognition ability of elementary school students was 83.84. Based on the results of the t test using paired sample test results obtained that p = 0.00Ë‚0.05 means that there are significant differences in the metacognition abilities of elementary school students between before and after treatment using scientific multiliteration learning models. That is, the scientific multiliteration learning model has a significant impact in developing the metacognition abilities of elementary school students